Grazing in California's Mediterranean Multi-Firescapes - Huntsinger, Lynn; Barry, Sheila (Frontiers in Sustainable Food Systems, 2021)
The California landscape is layered and multifunctional, both historically and spatially. Currently, wildfire size, frequency, and intensity are without precedent, at great cost to human health, property, and lives. We review the contemporary firescape, the indigenous landscape that shaped pre-contact California’s vegetation, the post-contact landscape that led us to our current situation, and the re-imagined grazing-scape that offers potential relief. Vegetation has been profoundly altered by the loss of Indigenous management, introduction of non-native species, implantation of inappropriate, militarized, forest management from western Europe, and climate change, creating novel ecosystems almost always more susceptible to wildfire than before. Vegetation flourishes during the mild wet winters of a Mediterranean climate and dries to a crisp in hot, completely dry, summers. Livestock grazing can break up continuous fuels, reduce rangeland fuels annually, and suppress brush encroachment, yet it is not promoted by federal or state forestry and fire-fighting agencies. Agencies, especially when it comes to fire, operate largely under a command and control model, while ranchers are a diverse group not generally subject to agency regulations, with a culture of autonomy in decision-making and a unit of production that is mobile. Concerns about potential loss of control have limited prescribed burning despite landowner and manager enthusiasm. Agriculture and active management in general are much neglected as an approach to developing fire-resistant landscape configurations, yet such interventions are essential. Prescribed burning facilitates grazing; grazing facilitates prescribed burning; both can reduce fuels. Leaving nature “to itself” absent recognizing that California’s ecosystems have been irrecoverably altered has become a disaster of enormous proportions. We recommend the development of a database of the effects and uses of prescribed fire and grazing in different vegetation types and regions throughout the state, and suggest linking to existing databases when possible. At present, livestock grazing is California’s most widespread vegetation management activity, and if purposefully applied to fuel management has great potential to do more.